The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1177/0886260520918573
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of Teen Dating Violence and Association With Depression Among Chinese Teens

Abstract: Teen dating violence (TDV) is a major global public health concern. Few studies, however, have examined profiles of TDV in Chinese societies and how these profiles might be associated with teens’ mental health. The current study analyzed a sample of 891 middle and high school students with dating experience in Taiwan, Hong Kong, and Shanghai. Latent class analysis (LCA) and multinomial logit regression analysis were performed in an attempt to identify profiles of TDV and then investigate possible associations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 68 publications
(93 reference statements)
2
5
0
1
Order By: Relevance
“…Again, this picture is consistent with the national data that used the same methodology and revealed prevalence rates between 68.8% and 71.8% among female adolescents and between 55.4% and 57.4% among male adolescents in the ninth and 11th grade in Switzerland (Ribeaud, 2015). However, these rates are much higher compared to international studies, for example, from the U.S. (Vivolo-Kantor et al, 2016;Zweig et al, 2013) or China (Cheng et al, 2020). The present data suggest that occasional monitoring of a dating partner is a very common behavior in the present sample of Swiss adolescents but future research is needed to replicate these results and, if applicable, to investigate the methodological and cultural background of the existing differences between the European, North American, and East Asian studies.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Again, this picture is consistent with the national data that used the same methodology and revealed prevalence rates between 68.8% and 71.8% among female adolescents and between 55.4% and 57.4% among male adolescents in the ninth and 11th grade in Switzerland (Ribeaud, 2015). However, these rates are much higher compared to international studies, for example, from the U.S. (Vivolo-Kantor et al, 2016;Zweig et al, 2013) or China (Cheng et al, 2020). The present data suggest that occasional monitoring of a dating partner is a very common behavior in the present sample of Swiss adolescents but future research is needed to replicate these results and, if applicable, to investigate the methodological and cultural background of the existing differences between the European, North American, and East Asian studies.…”
Section: Discussionsupporting
confidence: 87%
“…Monitoring and controlling behaviors are often included in rates of psychological aggression; however, some studies present separate results. For example, Cheng et al (2020) have found that the prevalence of different controlling behaviors (e.g., restricting the dating partner's actions) ranged between 8.7% and 12.2% among female adolescents and between 9.2% and 12.6% among male adolescents in a sample of Chinese teens with dating experience. The study by Zweig and colleagues (2013) found a similar prevalence rate for monitoring among male adolescents (11.0%) but a higher one among female adolescents (18.3%) in a United States (U.S.) sample of teens in a relationship.…”
Section: Scope Of Perpetrating Physical Violence and Monitoring In Te...mentioning
confidence: 99%
“…Currently, concern lies with not only the prevalence rates of dating violence among youth but also its consequences for mental health (Bonomi et al 2013;Goncy et al, 2017;Reys, Foshee, Chen, Gottfredson, & Ennett, 2018). Several psychological problems have been associated with dating violence, including symptoms of depression, anxiety, posttraumatic stress, eating disorders, alcohol and tobacco use, and risky sexual behavior (Bonomi et al, 2013;Cheng et al, 2020;Taquette & Monteiro, 2019). Adolescent victims present more symptoms of depression, eating disorders, and tobacco use in early adult life, compared to non-victims (Bonomi et al, 2013).…”
Section: ____________________________________________________________mentioning
confidence: 99%
“…Dating violence has been proven to be a serious public health problem because it contributes to maintaining violent adult marital relationships, as well as is associated with a number of consequences for the general and mental health of the victims (Bonomi, Anderson, Nemeth, Rivara, & Buettner, 2013;Cheng, Shen, & Jonson-Reid, 2020;Taquette & Monteiro, 2019). Dating violence includes a variety of abusive behaviors, such as psychological, physical, and sexual violence, within a context of current or past romantic or dating relationships between pre-teens, adolescents, and young adults (Centers for Disease Control and Prevention, Division of Violence Prevention, EUA, 2020; Mulford, & Blachman-Demner, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…These can be in the form of sleep disorders, eating disorders, weakened immune system, and low energy. These impacts can lead to a more serious impact, namely depression [9]. Sleep disorders do not only negatively affect adolescents' health but also disrupt their concentration level, thus disrupting their learning activity at school [10].…”
Section: Introductionmentioning
confidence: 99%